2015
DOI: 10.1080/01904167.2015.1061543
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with Phosphate Solubilizing Mesorhizobium Strains Improves the Performance of Chickpea (Cicer ariteniumL.) Under Phosphorus Deficiency

Abstract: The use of phosphate solubilising bacteria as inoculants increases plant phosphorus (P) uptake and thus crop yield. Strains from the genera Rhizobium are among the most powerful phosphate solubilizing microorganisms. In order to study efficiency in P uptake and nitrogen (N 2 ) fixation, forty-two rhizobia strains natively from Tunisian soils were studied in symbiosis with Cicer Downloaded by [UQ Library] at 03:34 13 July 2015 ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 2 aritenium variety i.e Béja1 frequently cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
1
7
0
1
Order By: Relevance
“…Our results accord with those of Imen et al (2015), who suggested the decisive importance of inoculation of Rhizobia on improving plant growth and the P uptake. In addition, other previous reports also emphasized that P-solubilizing microorganisms, such as genera Bradyrhizobium and Aspergillus, could elevate the growth of radish (Raphanus sativus), maize (Zea mays), lettuce (Lactuca sativa), and wheat (Triticum turgidum) (Antoun et al, 1998;Chabot et al, 1996Chabot et al, , 1998Sharma et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results accord with those of Imen et al (2015), who suggested the decisive importance of inoculation of Rhizobia on improving plant growth and the P uptake. In addition, other previous reports also emphasized that P-solubilizing microorganisms, such as genera Bradyrhizobium and Aspergillus, could elevate the growth of radish (Raphanus sativus), maize (Zea mays), lettuce (Lactuca sativa), and wheat (Triticum turgidum) (Antoun et al, 1998;Chabot et al, 1996Chabot et al, , 1998Sharma et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…To elucidate whether the A. aculeatus could enhance the performance of plants subjected to P-impoverished soils, we focused on the growth index, such as growth rate and turf quality. Phosphorus is an essential macronutrient necessary for plant growth, whose low availability or deficiency is a primary constraint to crop yield around the world (Imen et al, 2015;Wang et al, 2010). Previous studies have reported that beneficial effects of P on cell division and root elongation improved plant growth and yield (Sharma et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Direct mechanisms of plant growth by PGPR include the capacity to synthesize plant growth hormones such as auxins, gibberellins and cytokinins ( 11 , 12 ), enhancing symbiotic nitrogen fixation ( 13 ), solubilizing minerals (e.g., phosphorus, zinc, potassium, etc.) ( 14 , 15 ), siderophore production (iron chelators) ( 16 , 17 ) and production of ACC deaminase enzyme which helps in lowering ethylene levels in developing plant roots, resulting in increased root growth ( 18 , 19 ). The biocontrol capabilities of PGPR in response to biotic stress by generating antibiotics and cyanide, as well as fungal cell wall lysing enzymes that limit the growth of soil-borne phytopathogens, are the main indirect mechanisms ( 13 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…PGP bacteria colonize roots efficiently, enhance plants growth and yield. PGP rhizobacteria either directly or indirectly affect plants positively by increasing availability of nutrients ( Verma et al., 2013 ; Imen et al., 2015 ; Khalid et al., 2020 ), regulate nitrogenase activity, synthesize plant growth regulators like phytohormones ( Backer et al., 2018 ; Gopalakrishnan et al., 2018 ), siderophores ( Angus et al., 2013 ; Datta and Chakrabartty, 2014 ), hydrocyanic acid (HCN), 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity ( Tariq et al., 2014 ; Subramanian et al., 2015 ; Igiehon et al., 2019 ) and inhibit phytopathogens.…”
Section: Introductionmentioning
confidence: 99%